Exploring the demographics of conspiratorial beliefs about Covid-19 in the United States and European Union - Kukovič, Simona (Annales. Series historia et sociologia, 2024)
This study examines conspiratorial beliefs associated with the coronavirus pandemic in the United States, the European Union, and Slovenia. Drawing on a case-based approach, this research seeks to understand the underlying factors that have led to the emergence of conspiratorial beliefs regarding the coronavirus and the COVID-19 disease. We analysed surveys from the US and the EU to investigate the support of the general population towards the selected statements and beliefs closely connected to prevailing conspiracy theories. We seek the answer to the question of which demographic and societal factors contribute the most towards people’s beliefs about the origins of coronavirus.
Keywords: Covid-19; demografski dejavniki; demografski vidik; epidemija; Evropska unija; politična prepričanja; prepričanja; Teorije zarot